A comparative investigation of what lecturers assess as 'critical thinking' in student essays in higher education: a legitimation code theory analysis of the 'rules of the game' - Balawanilotu-Roach, Gina S. (2017)
Critical thinking is the most commonly listed of British university graduate attributes. However, its assessment in graduate students’ work in the disciplines remains underexplored in the literature. In the university, critical thinking is assessed within a disciplinary context and is synonymous with distinction or excellence. However, the discourse of ‘generic skills’ currently dominant in higher education has served to dissociate it from this base. The result is a single, generic understanding that may obscure crucial differences. Indeed, the often ignored question in discussions of critical thinking in student writing is ‘critical thinking about what?’ Karl Maton argues that overlooking ‘the what’ is prevalent in higher education research more broadly, resulting in what he terms ‘knowledge blindness’ (Maton, 2014c, p. 3). Knowledge, and its recontexualisation and reproduction in the curriculum, and teaching, sit at the heart of university practice. However, what knowledge practices are assessed as ‘critical thinking’ has remained mostly obscured in higher education research. The effect of ‘knowledge blindness’ is an unclear articulation of practices considered as ‘critical thinking’ in student writing in the disciplines. It is the central concern in this study.